Robust noble metal-based electrocatalysts for oxygen evolution reaction. (21st May 2019) - Shi, Qiurong; Zhu, Chengzhou; Du, Dan; Lin, Yuehe
Abstract : The oxygen evolution reaction (OER) is a kinetically sluggish anodic reaction that requires rationalized compositions and structures for achieving highly efficient and reliable noble metal-based electrocatalysts in acidic electrolyte. Abstract : The oxygen evolution reaction (OER) is a kinetically sluggish anodic reaction and requires a large overpotential to deliver appreciable current. Despite the fact that non-precious metal-based alkaline water electrocatalysts are receiving increased attention, noble metal-based electrocatalysts (NMEs) applied in proton exchange membrane water electrolyzers still have advantageous features of larger current and power densities with lower stack cost. Engineering NMEs for OER catalysis with high efficiency, durability and utilization rate is of vital importance in promoting the development of cost-effective renewable energy production and conversion devices. In this tutorial review, we covered the recent progress in the composition and structure optimization of NMEs for OER including Ir- and Ru-based oxides and alloys, and noble-metals beyond Ir and Ru with a variety of morphologies. To shed light on the fundamental science and mechanisms behind composition/structure–performance relationships and activity–stability relationships, integrated experimental and theoretical studies were pursued for illuminating the metal–support interaction, size effect, heteroatom doping effect, phase transformation, degradation processes and single-atom catalysis. Finally, the challenges and outlook are provided for guiding the rational engineering of OER electrocatalysts for applications in renewable energy-related devices.